Pengendalian Secara Biointensif Infeksi Begomovirus Pada Tanaman Cabai Merah Besar (Capsicum annuum L) Berbasis Tanaman Barier di Sulawesi Tenggara - Widodo, Catur Joko; Taufik, Muhammad (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
Biointensive Control of Begomovirus in Big Red Chili Plants (Capsicum annuum L) Based on Barrier Plants in Southeast Sulawesi. Begomovirus is a disease-causing agent from the plant virus group. This disease is one of the inhibiting factors for chili cultivation in various countries and regions in Indonesia. If chili plants are infected when they are still young, it can cause yield loss and crop failure. The spread of Begomovirus in the field is determined by whitefly insects. Controlling the population of vector insects is important to reduce infected plants. Barriers around chili plants can be used as vector barriers in the field. The purpose of this study was to evaluate the control of Begomovirus on large red chili peppers using the Biointensive barrier plant model. The method used was Randomized Block Design (RAK), analysis of variance and further BNT test with a confidence level of 95%. Observation variables included: symptoms, incidence and severity of Begomovirus disease, whitefly population and growth and production of chili. The results showed that the biotic barrier planting pattern of kenikir flowers affected the decrease in the whitefly insect population, incidence and severity (PepYLCIV) and increased red chili production. The lowest whitefly population was 0.45 individuals/plant compared to the control of 1.08 individuals/plant, the lowest incidence and severity (PepYLCIV) were 45% and 1.33% with the highest chili production (1.14 kg-plot) compared to the control (0.31 kg-plot).